2011
DOI: 10.1121/1.3653546
|View full text |Cite
|
Sign up to set email alerts
|

A connectionist study on the role of pitch in infant-directed speech

Abstract: Infant-directed speech (IDS) is believed to facilitate language learning. However, the benefit may be either due to clearer acoustic correlates to linguistic structures, or simply increased attention from infants induced by IDS exaggerated prosody. This study investigated the pure effect of IDS pitch on lexical tone learning, with attentional/ affective factors removed by using artificial neural networks. Following training with the pitch of Mandarin tones in IDS versus adult-directed speech, the networks yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…In fact, Kuhl et al (1997) also observed somewhat greater variability, and specifically hypothesized that stretched vowel spaces allow caregivers to produce more variable vowels, and thus improve category robustness, without increasing the amount of overlap between the categories (p. 685). Such differences across categories may partially account for why some computer learning studies report improved performance with IDS training (Boer & Kuhl, 2003), others deteriorated performance (Kirchhoff & Schimmel, 2005), and still others no difference (Gauthier & Shi, 2011). However, we have also shown that the increase in variability can occur in the absence of significant stretching of the distances separating phonological categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Kuhl et al (1997) also observed somewhat greater variability, and specifically hypothesized that stretched vowel spaces allow caregivers to produce more variable vowels, and thus improve category robustness, without increasing the amount of overlap between the categories (p. 685). Such differences across categories may partially account for why some computer learning studies report improved performance with IDS training (Boer & Kuhl, 2003), others deteriorated performance (Kirchhoff & Schimmel, 2005), and still others no difference (Gauthier & Shi, 2011). However, we have also shown that the increase in variability can occur in the absence of significant stretching of the distances separating phonological categories.…”
Section: Discussionmentioning
confidence: 99%
“…This was the case of the [i-I] contrast in both age groups. Such differences across categories may partially account for why some computer learning studies report improved performance with IDS training (Boer & Kuhl, 2003), others deteriorated performance (Kirchhoff & Schimmel, 2005), and still others no difference (Gauthier & Shi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In speech perception, pitch plays a role in prosody (Ohala, 1983), whereas variations in pitch provide linguistic meaning to words in tonal languages (Lee, Vakoch, & Wurm, 1996; Cutler & Chen, 1997; Ye & Connine, 1999). Pitch also plays a role in gender identification (Gelfer & Mikos, 2005) and may provide attention cues for infant-directed speech (Gauthier & Shi, 2011). In music perception, pitch is essential for melody recognition (Dowling & Fujitani, 1971; Cousineau, Demany, & Pressnitzer, 2009), and impairments in melody recognition in amusic listeners are related to deficits in pitch perception (Ayotte, Peretz, & Hyde, 2002; Peretz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To begin with, computational models of language development can be used to understand some of these relations in vitro. For example, the potential impact of caregivers' clarity of articulation on category learning has been studied by applying learning algorithms to data drawn from infant-directed speech (e.g., Gauthier & Shi, 2011, and citations therein). Furthermore, direct manipulations can be done using animal models, which should possess at least some of the prerequisites for certain skills involved in the acquired knowledge discussed earlier in the article.…”
Section: Toward Multivariate Modelsmentioning
confidence: 99%